(839) Experiences Concerned with Preparation and Carrying out of Investments التجارب المتعلقة بإعداد وتنفيذ الاستثمارات - Knauthe, Erhart (The Institute of National Planning, 2024)
his study addresses the problems that usually arise in the investment process and offers experiences from the GDR in this regard. The process of preparing and carrying out investments can be subdivided into at least three stages: Setting up technological and economic objectives. Elaboration of and decision on the project. Implementation of the project.